The Creative Research Process: Delights and Difficulties (LEARNing Landscapes, 2012)
This paper reports on an arts-informed approach to education research aimed to critically develop and promote teachers’ creative practice and understanding of creativity for both pupils and teachers. The creative research process is described to reveal how it developed 20 students as researchers in a secondary school in England. The students’ perspectives impressed artists and enlightened expert researchers into new ways of thinking and doing research. A reciprocal relationship was developed that unravelled novel data and promoted pupil voice.
Keywords: arts-informed; education; research; creative practice; creativity; secondary school; voice